Synthesis of palm-based zinc soaps for compounding in rubber products / Chua Wei Keong - Chua, Wei Keong (2014)

(untitled)
The melting point is the main factor in which metallic soap is to use as additives for the rubber manufacturing. This rubber compounder is the making stock for transfer moulding, compression, extruded profiles or hoses, the curing temperature or moulding and the duration will limit to the materials to be embedded on the surface of the compound. Zinc stearate has the lowest melting point as compared to other metallic soap. Although it has a low melting point, but it still consider high and problematic to the compounding system. The main objective in this study is to synthesis a various zinc fatty acids soap to have a lower melting point that possess the same functions as zinc stearate. The zinc content of zinc fatty acids soap will be analysed by using MP-AES. The composition of the fatty acids will be analysed by Gas Chromatography. The iodine value is to determine the completion of the reaction. The melting point also will be recorded by using Mettler Tolendo FP 80. The synthesised zinc fatty acids soap will be applied to the rubber compound to determine its performance ability.